Blood plasma hormones in relation to superovulatory response in crossbred cattle - RANJNA, S; CHEEMA, J S; RANJNA, MATHAROO; SINGH, PRAHLAD (The Indian Journal of Animal Reproduction, 2023)
Seven cows in group I and 9 cows in group II were superovulated with 400 mg of follfropin and 18 mg of ovagen,respectively. The blood was collected on day of first estrus (D-0). D-4. D-10, day of super estrus (DOSE) and day of embryocollection (DOEC) from the jugular vein. The blood plasma was analysed for progesterone, estrogen, T3 and T4 by using Elisa kits(Biochem lmmunosystems). Supcrovulation response was higher in the cows supcrovulated with ovagen than those with folltropin.The number of corpus luteum (CL) and embryos recovered were high in case of cows superovulated with ovagcn (8.2 ± 1.4, 3.2 ± 0.5)than with folltropin (7 .1 ± 3.4, 1.8 ± 0.6). The progesterone concentration in the blood plasma of highly responded cows (>6ovulations) was maximum on DOEC whereas it was low in the blood plasma of non responded ones. The animals superovulated withfolltropin . which resulted in >6 ovulations and 2 to 7 embryos, the plasma estrogen level was highest on DOSE. In the cows,superovulated with ovagen, resulting in 7-15 ovulations and 3-14 embryos, the blood plasma estrogen level was high on DOEC ascompared to low responded ones. T3 and T4 levels were found to be higher in the responded cows than in non-responded ones withboth the treatments. These studies indicate that high level of estrogen and low level of progesterone on DOSE can be used as a markerto predict the superovulatory response. It also emphasizes the need of systematic endocrine studies for creation of benchmark(s)and/or biomarkers as diagnostic tools in embryo transfer programme.
Keywords: Hormones; superovulation; embryo; cattle